The Role of the Ruler in Determining the Guardianship Rights of Girls Due to Pregnancy Outside of Wedlock: Case Study in KUA Mariso District, Makassar City - Pertiwi, Sri Adinda; Haddade, Abdul Wahid; Aisyah, Nur (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The determination of marriage guardians for girls due to pregnancy outside marriage is one of the problems that are the impact of pregnancy outside marriage. This study discusses the role of the ruler in determining guardianship rights for girls born due to pregnancy outside marriage; Case study in KUA, Mariso District, Makassar City. The purpose of this study is to determine the role of the head in KUA Mariso District, Makassar City in determining guardianship rights for girls born due to pregnancy out of wedlock. This type of research is field research which is processed through qualitative descriptive analysis which aims to produce descriptive data in the form of images, words and observed community behavior. The research approach used is a sociological approach and an approach that reviews and analyzes problems based on the results of research in the field. Primary and secondary data in this study were obtained through interviews and observation to obtain information. The results showed that the head of the Mariso Sub-district KUA determined the marriage guardian to the guardian of the judge because the child was only given to his mother and his mother’s family. The legal basis of the Mariso Sub-District KUA determines the guardianship rights to guardians in accordance with the Regulation of the Minister of Religious Affairs No. 30 of 2005 contained in the Compilation of Islamic Law. In the case of determining the guardian of marriage, the Head of the Mariso Sub-District KUA requires caution in examining and collecting information to determine the guardianship rights of girls born due to pregnancy outside the marriage of their parents, because it concerns whether or not the marriage of the girl child is legal.